Islamic Religious Education Teachers' Creativity in Overcoming Student Problems at SMPN 01 Jarai - Lola Miranda; Julius (Edumaspul: Jurnal Pendidikan, 2026)
This study examines the creativity of Islamic Religious Education (PAI) teachers in addressing student problems at SMPN 01 Jarai. The background stems from various student behavioral issues during learning, including boredom, drowsiness, chatting, and difficulty understanding material, which demand creative teacher intervention. This research aims to identify the manifestations of PAI teacher creativity and the supporting and inhibiting factors in overcoming student problems. Employing a qualitative approach with exploratory purpose, case study function, and descriptive method, data were collected through non-participant observation using APKG I and II instruments, structured interviews, and documentation from January to February 2026. The subject was purposively selected: the PAI teacher of Class VII. Data analysis followed Miles and Huberman's model of reduction, display, and verification. The findings reveal that: (1) teacher creativity is manifested through varied strategy combinations—Drill, SPBM, Cooperative Learning, CTL, and Project-Based Learning—progressively improving from 75% to 91.6%; (2) supporting factors include school facilities, policy freedom, MGMP collaboration, and intrinsic motivation, while inhibiting factors comprise limited projectors and irregular MGMP schedules. These creative practices effectively resolved student behavioral problems and enhanced learning engagement.